Management of Hypertension in the Elderly Patients: A Systematic Review - Dianah, Z; Umami, V (KnE Life Sciences, 2019)
Hypertension is one of the most common disease but it has adverse effects on target organs such as heart, brain, kidneys, and blood vessels if not treated properly. The management of hypertension could be different in some special population, such as in the elderly. In this population, there are special things to be considered, such as antihypertension drugs choices and blood pressure target. The purpose of this article was to provide information about the current management of hypertension in the elderly. The method used was systematic review with PRISMA protocol. Journal review results concluded that antihypertensive drugs therapy in elderly starts at blood pressure > 140/90 mmHg (130/85 mmHg if there is complication of diabetes, kidney disease, and cardiovascular); optimum target of systolic blood pressure is 120-140 mmHg and diastolic blood pressure not less than 65 mmHg; antihypertension drugs choices base on comorbidities and patient response to medication, and lifestyle modification is necessary to reduce cardiovascular risk and reduce the amount of drug consumed. Keywords: hypertension, elderly, management